Intrathecal clonidine as an adjuvant to hyperbaric bupivacaine in patients undergoing inguinal herniorrhaphy: A randomized double-blinded study - Anil Thakur; Mamta Bhardwaj; Kiranpreet Kaur; Jagdish Dureja; Sarla Hooda; Susheela Taxak (Wolters Kluwer Medknow Publications, 2013)
Background: Clonidine is added to intrathecal local anesthetics to improve intraoperative analgesia and to increase the duration of sensory and motor block. Aim of this study was to evaluate and compare the effects of addition of two different doses of clonidine (15 and 30 mcg) to 11 mg hyperbaric bupivacaine in patients undergoing inguinal herniorrhaphy surgery under spinal anesthesia. Materials and Methods: Seventy-five patients enrolled in the study were randomly divided into three groups of 25 each. Group I patients received 11 mg hyperbaric bupivacaine, whereas groups II and III received 15 mcg and 30 mcg clonidine, respectively, as an adjuvant to 11 mg hyperbaric bupivacaine. The volume of solution was kept constant to 2.4 ml by adding saline wherever needed. Results: Highest level of sensory block, time to achieve this level, and highest Bromage scale recorded were comparable among the groups. The mean time to two-segment regression, regression of sensory block to L3 dermatome, and mean duration of motor block were the greatest in group III followed by group II and group I. There was significant fall in mean arterial pressure (MAP) in groups II and III as compared to group I (P = 0.04). Episodes of hypotension were more in group III than in group II. Conclusion: 30 mcg clonidine was associated with more incidence and duration of hypotension than 15 μg of clonidine. 15 mcg clonidine added to 11 mg hyperbaric bupivacaine provides better sensory and motor blockade for inguinal herniorrhaphy.